(untitled) (GIST – Education and Learning Research Journal, 2024)
Effective writing is essential for academic and professional success, especially for students learning English as a Foreign Language (EFL). This study aimed to investigate the correlation between different writing strategies, EFL students’ self-efficacy in writing, and their actual writing performance. A descriptive-correlational research design was employed, involving 150 EFL students. Data were collected through questionnaires, IELTS writing tests, and interviews. The results showed a fragile but positive relationship between students’ self-efficacy and their use of writing strategies (r=0.119). Students who used various strategies, such as planning, revising, and self-monitoring, reported higher confidence in their writing abilities. Additionally, there was a significant but low correlation between the use of writing strategies and writing performance (r=0.114). However, writing strategies alone did not significantly predict improvements in writing abilities. These findings suggest that while enhancing students’ self-efficacy and encouraging effective writing strategies can potentially improve writing performance, writing strategies alone may not be sufficient. Therefore, English teachers should focus on both training and motivating students to use effective writing strategies to address writing challenges effectively.